Effect of Nanoadditives on the Wear Behavior of Spheroidal Graphite Cast Irons - J. Kaleicheva; V. Mishev; Z. Karaguiozova; G. Nikolcheva; A. Miteva (Tribology in Industry, 2017)
The tribological characteristics of spheroidal graphite cast irons with and without nanosized additives are investigated. The tests are performed as in cast iron condition as well after austempering. The spheroidal graphite irons are undergone to austempering in the bainite field, including heating at 900 °С for an hour, after that isothermal retention at 280 °С, 2 h and at 380 °C, 2 h. The lower bainitic and upper bainitic structures are formed during the process. Nanosized additives of titanium carbonitride and titanium nitride TiCN+TiN influence on the graphite phase characteristics and on the microstructure of the cast and austempered spheroidal graphite irons. The changes in the micro structure the irons with nanoadditives lead to an abrasive wear resistance increase. The formation of the strain induced martensite from the retained austenite in the friction contact area during wear is determined in the austempered irons. This is the reason for the wear resistance increase of the irons. The experimental testing of the wear is carried out by cinematic scheme tapper-discunder friction on the fixed abrasive. The microstructure of the patterns is observed by optical and quantitative metallography, X-Ray analysis, SEM and EDX analysis. The hardness testing is performed by Brinnel and Vickers methods.